The Relationship between Self-Regulation and Fear of Missing Out in the Use of Social Media TikTok among Students of University (Lembaga Pengembangan Kinerja Dosen, 2026)
The phenomenon of Fear of Missing Out (FoMO) is increasingly experienced by university students along with the rising use of TikTok as a source of entertainment and information. The fast and constantly changing flow of content often makes users feel the need to always keep up with developments so as not to be left behind. In this condition, self-regulation is viewed as an important ability that can help reduce the tendency for FoMO to emerge. This study aims to determine the relationship between self-regulation and FoMO among university students who use TikTok. A total of 206 students participated by completing an online questionnaire that used the Short Self-Regulation Questionnaire (SSRQ) and the Fear of Missing Out Scale (FoMOS). The normality test showed that both variables were not normally distributed; therefore, the analysis was continued using Spearman correlation. The results showed a significant negative relationship between self-regulation and FoMO (r = –0.370; p = 0.000). These findings indicate that the better the students’ ability to regulate themselves, the lower their tendency to experience FoMO when using TikTok. Overall, this study emphasizes that self-regulation has an important role in helping students deal with the dynamics of social media use and can serve as a basis for developing strategies to encourage more balanced social media use.